The Relationship between Macroeconomic Variables and ESG Index: Evidence from Six Emerging Markets - Ahmad Bit, Nabiel Elhakim Al; Pasaribu, Pananda (Quantitative Economics and Management Studies, 2024)
This study examines the relationship between ESG index return and macroeconomic factors in six emerging markets (Indonesia, Brazil, China, Mexico, South Africa, and India). Previous study has shown that the impact of macroeconomic variables on stock/index returns differs according to the country's economic structure and condition. The primary motivation for this study is the growing trend of ESG investment and the contradictory findings of the macroeconomic component influence on stock return. This study utilizes Panel Data Regression to investigate the association between macroeconomic variables and ESG index returns over a five-year period. This analysis reveals that inflation and Gross Domestic Product (GDP) have a positive significant influence on the ESG index return, however, interest rate and foreign exchange rate are not statistically significant. These findings provide useful insight to many stakeholders, including investors, policymakers, and financial experts, on how to develop investment strategies and economic policies to reap economic benefits such as better investment and improved ESG framework implementation in organizations.